Explosive exercise - Stone, Mi.; Stone, Me.; Lamont, H. (coachesinfo.com)
Before discussing explosive exercise in detail terms are defined and a theoretical background is presented. After that explosive strength and the way of measuring explosive strength are explained.The specifity of training is discussed as well as possible training adaptations. Speed strength exercises are proposed, the specificity of strength/power training is explained as well as the factors effecting the explosiveness and the injury potential of resistance training. Summary: In summarising various aspects of explosive exercise it should be noted that: 1. different training programmes can elicit very specific long-term adaptations 2. different trained states alter training adaptations 3. in order to elicit maximum responses all strength training should incorporate maximum efforts regardless of the weight used 4. training for maximum explosiveness requires emphases on both maximum strength and explosive training 5. straining advanced athletes requires creative planning. This planning should incorporate a periodised sequenced structure.